A new species of Grandidierella Coutière, 1904, G. nioensis sp. nov. (Amphipoda, Aoridae), from the east coast of India - Myers, Alan A.; Sreepada, Rayadurga A.; Sanaye, Sushant V. (Zootaxa, 2019)
A new species of Grandidierella Coutière, 1904, G. nioensis is described from the east coast of India. It is close to G. mahafalensis Coutière, 1904, from Madagascar and G. halophilus Wongkamhaeng, Pholpunthin & Azman, 2012 from Thailand. A key is provided to facilitate the identification of species in the Grandidierella mahafalensis Coutière, 1904 species-complex.